Religiosity and Psychological Contracts in Asian B2B Service Relationships - Kingshott, Russel; Chung, Henry; Putranta, Martinus Parnawa; Sharma, Piyush; Sima, H. (Elsevier, 2021)
The growing significance of Asia in global trade has meant that service organizations within the region need to build robust relationships with customers that may reside in nations with different socio-cultural backgrounds. This paper draws on the theories of social exchange and social capital to examine how Indonesian service providers build B2B relationships with their Asian customers in the region, when the customers are from non-Islamic nations. This study used a survey to collect its primary data. Data from 312 Indonesian firms revealed that Asian cultural-specific concepts of religiosity not only had a positive impact on transactional and relational psychological contracts, but also dampened psychological contract breaches. Only relational psychological contracts had a positive effect on relational capital and relational wellbeing, despite transactional contracts being intrinsic to these relationships. Relational capital helped to reduce psychological contract breaches and improve relationship wellbeing, whereas psychological contract breaches reduced such wellbeing. Our findings significantly extend research on B2B service relationships and offer valuable managerial insights for service decision makers operating in Asia that involves B2B relationships between organizations with specific and different socio-cultural backgrounds.